Effects of warming and isolation from precipitation on the soil carbon, nitrogen, and phosphorus, and their stoichiometries in an alpine meadow in the Qinghai–Tibet Plateau: A greenhouse warming study - Tong, Yongpeng; Long, Yanjun; Yang, Zhen’an (Frontiers in Ecology and Evolution, 2023)
Introduction In the Qinghai–Tibet Plateau (QTP), alpine meadows are among the most noticeable reflection of global climate change. However, effects of global warming on soils hosting alpine meadows in the QTP, such as reduced moisture because of low precipitation, remain unclear. Methods Here, the soil moisture content (SMC), pH, dissolved organic carbon (DOC), ammonium nitrogen (NH4+–N), nitrate nitrogen (NO3−–N) and available phosphorus (AP) contents in the QTP were analyzed. The changes in and stoichiometries of total carbon, nitrogen, and phosphorus (TC, TN, and TP), microbial biomass carbon, nitrogen, and phosphorus (MBC, MBN, and MBP), β-1,4-glucosidase (BG), β-1,4-N-acetylglucoaminosidase (NAG), leucine aminopeptidase (LAP), and acid phosphatase (ACP) in the 0–30 cm layer of soils associated with warming in a greenhouse in the QTP from 2015 to 2020 were characterized. Results We found that warming in the greenhouse significantly decreased the SMC, NO3−–N, MBC, MBN, MBP, BG, LAP, ACP, and enzymatic C:N ratio. The warming increased the DOC, NH4+–N, AP, MBC:MBN, and enzymatic N:P ratios noticeably. The pH, TC, TN, TP, C:N, C:P, N:P, MBC:MBP, MBN:MBP, and enzymatic C:P ratios were minimally affected. Conclusion The results showed that warming and isolation from precipitation promoted mineralization of N and P in the soil but did not significantly alter the cycling of elements in soils in an alpine meadow.